0361 A 49 year follow-up of mortality in the british rubber industry. (21st August 2017) - Mueller, Will; McElvenny, Damien; Ritchie, Peter; Cherrie, John; Hidajat, Mira; Agius, Raymond; Darnton, Andrew; Vocht, Frank de
Abstract : Rubber workers in Great Britain were historically exposed to various carcinogenic substances, including β-naphthylamine, which was removed from industrial processes in 1949. The Health and Safety Executive (HSE) initiated in 1967 a prospective occupational cohort study of British rubber industry workers, including men 35 years of age and older, to examine cancer mortality (n=40 867, representing 381 factories). Findings from a 10 year follow-up of that cohort suggested excess mortality from cancers of the bladder, lung, and stomach, which differed by exposure to naphthylamines, as well as by industry sector and job code. The purpose of this analysis is to extend mortality follow-up through to 2015, allowing an assessment of cancers in older ages and with longer latency periods. As well as headline Standardised Mortality Ratios (SMRs) for the cancer subtypes previously investigated, we will present mortality risks for a range of causes including leukaemia, multiple myeloma, circulatory and respiratory diseases. We will use England and Wales reference rates to compare mortality by employment duration and sector in the rubber industry. Preliminary analysis of a majority subset of the cohort (n=34, 595) to 2015 identified an elevated all cause SMR of 1.11 (95%CI 1.10–1.12). More detailed results from this multi-decade follow-up of workers from rubber manufacturing will provide valuable insights into cancer mortality risks for exposed occupational populations, both in the UK and elsewhere.